GPS network-based approach to mitigate residual tropospheric delay in low latitude areas - Musa, Tajul A. (Institute of Navigation, USA, 2005)
A strong spatio-temporal variation of the wet component in the troposphere leaves us in a peculiar predicament. The residual tropospheric delay will remain in the measurements and therefore affect the estimation of related parameters. In the areas of hot and wet climate conditions, especially in the equatorial or low latitude regions, the strong tropospheric effect on GPS measurements is unquestionable. This study proposes geometric modeling through the network-based approach to mitigate the residual tropospheric delay in such regions. A part of Southeast Asia is selected as a test area for the study, which covers Malaysia and Singapore. Tests are conducted in post-processing but in the â€œsimulating RTKâ€? mode, and evaluated by the number of ambiguity fixes and the accuracy of the coordinate results. Network-based RTK positioning in low latitude areas has shown that the proposed technique can enhance ambiguity resolution by pivoting the ionosphere-free measurements through the mitigated residual tropospheric delay.